2007
DOI: 10.1038/nmeth1107
|View full text |Cite
|
Sign up to set email alerts
|

In vivo gene regulation in Salmonella spp. by a salicylate-dependent control circuit

Abstract: Systems allowing tightly regulated expression of prokaryotic genes in vivo are important for performing functional studies of bacterial genes in host-pathogen interactions and establishing bacteria-based therapies. We integrated a regulatory control circuit activated by acetyl salicylic acid (ASA) in attenuated Salmonella enterica that carries an expression module with a gene of interest under control of the XylS2-dependent Pm promoter. This resulted in 20-150-fold induction ex vivo. The regulatory circuit was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
83
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 29 publications
0
83
0
2
Order By: Relevance
“…For example, combinations of two or more promoters that are preferentially induced in tumors by different regulatory mechanisms would allow the delivery of two or more separate protein components of a therapeutic system under different regulatory pathways. In addition, new promoter systems induced by external agents such as arabinose (30) or salicylic acid (31) allow promoters in Salmonella to be induced throughout the body at the time of choice. Such inducible regulation could be combined with tumor-specific Salmonella promoters to express useful products in …”
Section: Resultsmentioning
confidence: 99%
“…For example, combinations of two or more promoters that are preferentially induced in tumors by different regulatory mechanisms would allow the delivery of two or more separate protein components of a therapeutic system under different regulatory pathways. In addition, new promoter systems induced by external agents such as arabinose (30) or salicylic acid (31) allow promoters in Salmonella to be induced throughout the body at the time of choice. Such inducible regulation could be combined with tumor-specific Salmonella promoters to express useful products in …”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 4, the inducer is capable to exert its activity on intracellular bacteria in mammalian cultured cells. 43 In addition, mice bearing tumors were infected with the S. enterica strain SL7207-4S2 carrying the P m -gfp encoding plasmid. Then, the system was induced by administering salicylate and after 4 h flow cytometry analysis showed that 30% of the tumor cells were GFP-positive.…”
Section: Over-imposed Circuit To Improved Salicylate-dependent Cascadementioning
confidence: 99%
“…Then, the system was induced by administering salicylate and after 4 h flow cytometry analysis showed that 30% of the tumor cells were GFP-positive. 43 Thus, it could be conceived that the nahR/P sal ::xylS2 expression system together with Salmonella spp. could be used in the context of anticancer therapy, by benefiting from Salmonella properties to find a niche in hypoxic and necrotic areas located inside some solid tumors.…”
Section: Over-imposed Circuit To Improved Salicylate-dependent Cascadementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it would be beneficial to exogenously regulate their gene expression to, e.g., reduce side effects. In bacteria, inducible systems were introduced that could be activated by nontoxic sugar compounds such as L-arabinose (1) and L-rhamnose (2), by tetracycline derivatives (2), or by acetyl salicylic acid (3). Oncolytic adenoviruses have also been equipped with inducible gene expression systems that rely on the administration of tetracycline derivatives (4,5), the absence of theophylline (6), or the application of heat (7).…”
mentioning
confidence: 99%